EPIDEMIOLOGI, PATHOGENESIS AND RISK FACTOR OF OSTEOARTHRITIS - Njoto, Ibrahim (Universitas Wijaya Kusuma Surabaya, 2013)
Osteoarthritis is the common form of arthritis. Indonesian prevalention of radiologic knee osteoarthritis was 15.5% in man and 12.7% in women. Indonesian prevalention of osteoarthritis was high and need special attention because of the complication which occurred, such as patient handicap and movement problems. While increasing of Indonesian time period of life expentancy caused higher number of osteoarthritis population. According to data of WHO: Indonesian time period of life expentancy was 68 years old at 2009 which asummed follow by one to two million handycap patient. This number getting higher and higher in the future equal with increasing of senille population in Indonesia. Osteoarthritis is caused by multifactorial and chronic progressive disease, so it badly impact to patient morbidity. Pathogenesis of osteoarthritis not clear enough, some scientists declared that osteoarthritis was a degenerative disease and the others declared as an inflamation disease. According to many predispossing factors caused to ostheoarthritis, an adequate prevention was available to depress number of osteoarthritis case in the future. Therefore some continuing study of epidemiology, pathogenesis, risk factors as basic science, to provide development of compact pathogenesis process to support an adequate preventional management in the future.